2005
DOI: 10.1164/rccm.200501-004oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prone Position on Regional Shunt, Aeration, and Perfusion in Experimental Acute Lung Injury

Abstract: Rationale:The prone position is used to improve gas exchange in patients with acute respiratory distress syndrome. However, the regional mechanism by which the prone position improves gas exchange in acutely injured lungs is still incompletely defined. Methods: We used positron emission tomography imaging of [ 13 N]nitrogen to assess the regional distribution of pulmonary shunt, aeration, perfusion, and ventilation in seven surfactant-depleted sheep in supine and prone positions. Results: In the supine positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
134
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 40 publications
15
134
1
6
Order By: Relevance
“…Animal studies have demonstrated improved oxygenation and ventilation perfusion ratios, along with restoring aeration, decreasing shunt, and preserving perfusion 1,9,15 . In addition, prone positioning has been shown to eliminate compression of the lungs by the heart 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have demonstrated improved oxygenation and ventilation perfusion ratios, along with restoring aeration, decreasing shunt, and preserving perfusion 1,9,15 . In addition, prone positioning has been shown to eliminate compression of the lungs by the heart 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of prone ventilation has been shown to improve aeration and decrease alveolar shunt in an animal model 9 . Many clinical and experimental studies have since been carried out, but the mechanism responsible for the improvement remains highly controversial 4,10 .…”
Section: Introductionmentioning
confidence: 99%
“…When patients are placed in the prone position, the chest wall compliance decreases, and the P TP is redistributed from dorsal to ventral and, as a consequence, there is a recruitment of pulmonary dorsal regions, which directly reflects the improvement in patient's oxygenation [10][11][12] . By promoting a more balanced ventilation associated with recruitment, the prone position also results in a better distribution of blood flow 13 , preventing its inappropriate redirection from hyperinflated areas to the collapsed ones in response to increased average airway pressure and positive end-expiratory pressure (PEEP) 14,15 . In addition to direct effects, studies show that the ventilation in prone protects from, or at least slows the development of, injuries associated with mechanical ventilation 16 .…”
Section: Methods Methods Methods Methodsmentioning
confidence: 99%
“…Th e reduction or delay in the development of VILI in the prone position can be explained by diff erent mechanisms: (a) A more homogeneous distribution of transpulmonary pressure gradient due to changes in the lung-thorax interactions and direct transmission of the weight of the abdominal contents and heart [22], yielding a redistribution of ventilation; (b) increased endexpiratory lung volume resulting in a reduction in stress and strain [25]; and (c) changes in regional perfusion and/or blood volume [26]. In a paraquat model of ALI, the prone position was associated with a better perfusion in ventral and dorsal regions, a more homogeneous distribution of alveolar aeration which reduced lung mechanical changes and increased end expiratory lung volume and oxygenation [27].…”
Section: Patient Positioningmentioning
confidence: 99%
“…Some authors have reported that in healthy [23], as well as in lung-injured animals [24], mechanical ventilation leading to lung overdistension and cyclic collapse/reopening was associated with less extensive histological change in dorsal regions in the prone, as compared to the supine position. Although the claim that body position aff ects the distribution of lung injury has been challenged, the development of VILI due to excessively high V T seems to be delayed during prone compared to supine positioning [25].Th e reduction or delay in the development of VILI in the prone position can be explained by diff erent mechanisms: (a) A more homogeneous distribution of transpulmonary pressure gradient due to changes in the lung-thorax interactions and direct transmission of the weight of the abdominal contents and heart [22], yielding a redistribution of ventilation; (b) increased endexpiratory lung volume resulting in a reduction in stress and strain [25]; and (c) changes in regional perfusion and/or blood volume [26]. In a paraquat model of ALI, the prone position was associated with a better perfusion in ventral and dorsal regions, a more homogeneous distribution of alveolar aeration which reduced lung mechanical changes and increased end expiratory lung volume and oxygenation [27].…”
mentioning
confidence: 99%